Determination of health anxiety, anxiety, and somatosensory amplification levels in individuals with normal coronary angiography - Korkmaz, Hasan; Korkmaz, Sevda; Yildiz, Sevier; Gundogan, Burcu; Atmaca, Murad (Elsevier Ireland Ltd, 2017)
The objective of the present study is to determine the somatosensory amplification, anxiety, and depression levels in patients with normal coronary arteries. Thirty-five patients with normal coronary arteries and 35 healthy individuals of similar age and gender as the patient group were included in the study. Somatosensory Amplification Scale (SSAS), Health Anxiety Inventory (HAI-18), Penn State Anxiety Scale (PSWQ), Beck Anxiety Inventory (BAI), and Beck Depression Inventory (BDI) were applied to all participants. Comparison of the patient group with the control group demonstrated that SSAS (22.7 +/- 8.2; 18.5 +/- 5.98; p = 0.018), BAI (15.4 +/- 9.43; 9.4 +/- 7.3; p = 0.004), BDI (24.9 +/- 13.5; 13.7 +/- 7.5; p < 0.001), PSWQ (55.3 +/- 13.7; 33.8 +/- 6.7; p < 0.001), and HAI-18 (18.8 +/- 8.7; 12.3 +/- 7.1; p = 0.001) scores were statistically significantly higher in the patient group. Furthermore, a positive correlation was found between SSAS, BAI, BDI, PSWQ, and HAI-18 scores. It was found that concerns about disease prevailed in patients having normal coronary arteries, the patients continued to amplify their somatic sensations, and their anxiety and depression scores were higher than those of healthy individuals. Thus, the necessity of these interventions should be assessed in detail in the future.
Keywords: Coronary angiography; Somatization; Anxiety; Health anxiety